The Power of Faith: The Influence of Athletes’ Coping Self-Efficacy on the Cognitive Processing of Psychological Stress - Guo, Tengfei; Ni, Yakun; Li, Qiaoling; Hong, Hao (Frontiers in Psychology, 2019)
Abstract Coping self-efficacy (CSE) has a positive mental health effect on athletes' ability to cope with stress. To understand the mechanism underlying the potential impact of CSE, event-related potentials (ERPs) were used to explore the neural activity of the cerebral cortex under acute psychological stress in athletes with different CSE levels. Among 106 high-level athletes, 21 high CSE athletes and 20 low CSE athletes were selected to participate in the experiment. A mental arithmetic task was used to induce acute psychological stress. The results showed that high CSE athletes responded more quickly than low CSE athletes. In the stress response stage, the N1 peak latency of low CSE athletes was longer than that of high CSE athletes, and the N1 amplitude was significantly larger than that of high CSE athletes. In the feedback stage, the FRN amplitude with error feedback of high CSE athletes was larger than that of low CSE athletes, and the P300 amplitude with correct feedback was larger than that with error feedback. The results indicate that high CSE athletes can better cope with stressful events, adjust their behaviors in a timely manner according to the results of their coping, and focus more on processing positive information.